Gravitational field-flow fractionation in combination with flow injection analysis or electrothermal AAS for size based iron speciation of particles - Chantiwas R. (2014)
A simple gravitational field-flow fractionation (GrFFF) system was used for size separation of micron sized silica particles coated with hydrous iron oxide (geothite). The amount of iron on the particles was monitored either on-line by reverse-flow injection analysis (r-FIA) with chemiluminescence detection using luminol or off-line by electrothermal atomic absorption spectrophotometry (ETAAS). The combination of GrFFF with reverse FIA or with ETAAS has been demonstrated to be a cost-effective tool for size based iron speciation of particles. © 2002 Elsevier Science B.V. All rights reserved.